Sex Determination from Radiological Assessment of the Sacrum in Nepalese Population: A Crosssectional Study - Shrestha, Subina; KC, Sudikshya; Acharya, Sumnima (Journal of Lumbini Medical College, 2020)
Introduction: Human skeleton shows variable degree of sexual dimorphism, but definitive inference can be obtained from only a few bones, sacrum being one of them. The morphometric differences of the bone will be helpful to obstetricians, as it shows special adaptations in females for child bearing. It is also important for physical anthropologists and forensic scientists for sex determination. The aim of this study was to find out whether sex could be determined by using sacral parameters from X-ray images of pelvis. Methods: The study included antero-posterior X-ray images of pelvis with clearly visible 680 sacra (311 of males and 369 of females) obtained by computer generated random numbers from records in the Department of Radiodiagnosis of a medical college in Nepal. X-ray images with the sacrum suspected for fractures and pathological diseases were excluded. Inbuilt software “CR Konica Minolta Aero DR/CR CS7” was used for measurements. Results: The mean sacral length and mean transverse diameter of S1 vertebra were higher in males; whereas, mean sacral breadth, mean left ala length, mean right ala length, mean ala length, mean sacral index and mean alar index were higher in females. These differences in sacral parameters between the two sexes were statistically significant (p<0.05). The percentage of bones identified by demarking points of sacral index was 15.17% and 0.32% respectively in the males and the females. Conclusion: The result of the present study supported determination of sex of an individual from radiological assessment of sacrum.